2018
DOI: 10.1007/s12282-018-0898-9
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor-negative/progesterone receptor-positive phenotype of invasive breast carcinoma in Japan: re-evaluated using immunohistochemical staining

Abstract: The ER-/PgR+ phenotype was confirmed after re-evaluation of ER and PgR assessment by a different pathologist. We recommend that pathologists discuss with clinicians, or re-test and re-evaluate ER/PgR expression, particularly in low-grade carcinoma and with a high staining proportion of PgR in the ER-/PgR+ phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Such large cohorts are useful to provide data on uncommon subtypes or phenotypes. For example, the prevalence of ER−/PR+ cases in this database is low ( n = 213, 1.7% in the whole ESME cohort), as reported in the literature with a prevalence ranging from 0.3 to 3.4% 27 29 .The ER−/PR+ phenotype is still a controversial molecular subtype, as some data suggest that this phenotype might be mainly due to technical artifacts 20 , 30 , while other studies confirmed it as a true but rare biologic subtype 27 29 . Moreover, the largest studies to date on this rare phenotype reported a trend for a poorer prognosis (early recurrence, poorer overall and disease free survival) as compared with ER+/PR+ tumors, and more similar to ER-/PR- tumors 28 , 29 .…”
Section: Discussionsupporting
confidence: 45%
“…Such large cohorts are useful to provide data on uncommon subtypes or phenotypes. For example, the prevalence of ER−/PR+ cases in this database is low ( n = 213, 1.7% in the whole ESME cohort), as reported in the literature with a prevalence ranging from 0.3 to 3.4% 27 29 .The ER−/PR+ phenotype is still a controversial molecular subtype, as some data suggest that this phenotype might be mainly due to technical artifacts 20 , 30 , while other studies confirmed it as a true but rare biologic subtype 27 29 . Moreover, the largest studies to date on this rare phenotype reported a trend for a poorer prognosis (early recurrence, poorer overall and disease free survival) as compared with ER+/PR+ tumors, and more similar to ER-/PR- tumors 28 , 29 .…”
Section: Discussionsupporting
confidence: 45%
“…The other important nuclear receptor, the progesterone receptor (PR) is expressed in about 70 per cent of ERpositive cases. Whether PR can be expressed in ER-negative cases has long been a point of debate but this phenotype seems to exist rarely [3]. About 20 per cent of breast tumors over-express the HER2/NEU receptor (erbB2) for epidermal growth factor (EGF).…”
Section: Introductionmentioning
confidence: 99%
“…were initially diagnosed with ER-PR+ breast carcinoma, and 7 patients remained ER-PR+ (13). However, another study found that breast carcinoma of ER-PR+ existed, although rare (1.1% of all phenotypes), and had distinct clinicopathologic characteristics (14).…”
Section: Kaplan-meier Curves Of Os and Bcss After Psmmentioning
confidence: 99%